Achieving resiliency in major defense programs through nonfunctional attributes. Issue 5 (14th April 2019) - Enos, James R.
Abstract: This article examines how the ilities, or nonfunctional attributes, help to understand the concept of resiliency in engineered systems. For engineered systems, resiliency describes the ability of a system to react to and return to full function after an interruption to system operation. The literature on resiliency of engineered systems defines resiliency in both the context of mission and platform resiliency; however, it leaves an opportunity to research how to understand, manage, and achieve resiliency. This work proposes an application of the systems engineering ilities to resiliency to understand how systems engineers can account for resiliency in the design process and incorporate resiliency into systems. Quality, robustness, and agility assist in understanding the components of resiliency and the ilities of repairability, extensibility, flexibility, adaptability, and versatility provide means for systems to achieve resiliency. This article applies this framework to examine two cases of DoD systems, the B‐52 bomber and the F‐117 stealth fighter. These two examples demonstrate how nonfunctional attributes enable engineered systems to achieve resiliency and help to better understand the concept of resiliency in engineered systems.